Martial Book XII : a commentary - Bowie, MNR (1988)
The commentary consists of an introduction and individual line by line commentaries on the prose preface and the 98 epigrams. The introduction comprises a brief discussion of the dating of book 12, its distinctively Spanish elements, and the arrangement of the poems, and a more detailed treatment of the textual tradition of Martial. The commentary addresses matters of textual, literary and social-historical interest as they arise, and provides a large quantity of parallels on points of usage. It attempts in particular to identify and explain the point of the comic poems, both as jokes and as literary works. It also examines poems in their relation to the rest of book 12 and to the whole of Martial's opus. A select bibliography is appended.